2021
DOI: 10.12688/wellcomeopenres.16731.1
|View full text |Cite
|
Sign up to set email alerts
|

The management of tetanus in adults in an intensive care unit in Southern Vietnam

Abstract: Background: Tetanus remains common in many low- and middle-income countries (LMICs) yet the evidence base guiding management of this disease is extremely limited, particularly with respect to contemporary management options. Sharing knowledge about practice may facilitate improvement in outcomes elsewhere. Methods: We describe clinical interventions and outcomes of 180 adult patients ≥16 years-old with tetanus enrolled in prospective observational studies at a specialist infectious diseases hospital in Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…For the 6 patients who had severe stomach retention in this study, we used the nasojejunal tube for postpyloric feeding to strengthen nutritional support. The overall median duration of hospitalization of patients with tetanus in this study was 29.5 days, which was similar to a recent report of low mortality (2.8%) from Vietnam ( 30 ). The median hospital stay of the latter was 25 days, which was much longer than the hospitals reported in some areas with high mortality ( 10 , 18 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the 6 patients who had severe stomach retention in this study, we used the nasojejunal tube for postpyloric feeding to strengthen nutritional support. The overall median duration of hospitalization of patients with tetanus in this study was 29.5 days, which was similar to a recent report of low mortality (2.8%) from Vietnam ( 30 ). The median hospital stay of the latter was 25 days, which was much longer than the hospitals reported in some areas with high mortality ( 10 , 18 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, there is no uniform guideline for wound debridement in patients with tetanus. Some published studies on the prognosis of tetanus have not reported the rate of implementation of debridement ( 10 , 29 , 30 ). We believe that debridement is essential to control the symptoms of tetanus and improve the prognosis, especially for severe tetanus.…”
Section: Discussionmentioning
confidence: 99%
“…Spasms were treated with benzodiazepines as first-line agents, escalating to mechanical ventilation with nondepolarizing neuromuscular blocking agents. 10 ANSD was treated with magnesium sulphate titrated against clinical effect and serum magnesium of < 4 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…In Vietnam, despite the extensive nationwide childhood immunization program, tetanus is not rare and remains a life-threatening disease [ 1 ]. There are approximately 250–350 cases admitted to the Hospital for Tropical Diseases (HTD)—the largest center for infectious diseases in southern Vietnam annually [ 3 ]. Most patients aged ≥16 years demonstrate an absence of primary series and booster tetanus vaccination in the community [ 4 ].…”
mentioning
confidence: 99%
“…Most patients aged ≥16 years demonstrate an absence of primary series and booster tetanus vaccination in the community [ 4 ]. Recently, respiratory arrest, which used to be the most common cause of death from tetanus, has been well managed by tracheostomy procedure and ventilation [ 3 ]. Hence, cardiovascular system–related complications have been documented as a main cause of morbidity and mortality, although the etiology of cardiovascular events (CEs) in tetanus remains unclear [ 5 ].…”
mentioning
confidence: 99%